SARS-CoV-2 infection in children: A 24 months experience with focus on risk factors in a pediatric tertiary care hospital in Milan, Italy - Di Pietro, Giada Maria; Ronzoni, Luisa; Meschia, Lorenzo Maria; Tagliabue, Claudia; Lombardi, Angela; Pinzani, Raffaella; Bosis, Samantha; Marchisio, Paola Giovanna; Valenti, Luca (Frontiers in Pediatrics, 2023)
Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in children is characterized by a wide variety of expressions ranging from asymptomatic to, rarely, critical illness. The basis of this variability is not yet fully understood. The aim of this study was to identify clinical and genetic risk factors predisposing to disease susceptibility and progression in children. Methods We enrolled 181 consecutive children aged less than 18 years hospitalized with or for SARS-CoV-2 infection during a period of 24 months. Demographic, clinical, laboratory, and microbiological data were collected. The development of coronavirus disease 2019 (COVID-19)-related complications and their specific therapies were assessed. In a subset of 79 children, a genetic analysis was carried out to evaluate the role of common COVID-19 genetic risk factors (chromosome 3 cluster; ABO-blood group system; FUT2, IFNAR2, OAS1/2/3, and DPP9 loci). Results The mean age of hospitalized children was 5.7 years, 30.9% of them being under 1 year of age. The majority of children (63%) were hospitalized for reasons different than COVID-19 and incidentally tested positive for SARS-CoV-2, while 37% were admitted for SARS-CoV-2 infection. Chronic underlying diseases were reported in 29.8% of children. The majority of children were asymptomatic or mildly symptomatic; only 12.7% developed a moderate to critical disease. A concomitant pathogen, mainly respiratory viruses, was isolated in 53.3%. Complications were reported in 7% of children admitted for other reasons and in 28.3% of those hospitalized for COVID-19. The respiratory system was most frequently involved, and the C-reactive protein was the laboratory test most related to the development of critical clinical complications. The main risk factors for complication development were prematurity [relative risk (RR) 3.8, 95% confidence interval (CI) 2.4–6.1], comorbidities (RR 4.5, 95% CI 3.3–5.6), and the presence of coinfections (RR 2.5, 95% CI 1.1–5.75). The OAS1/2/3 risk variant was the main genetic risk factor for pneumonia development [Odds ratio (OR) 3.28, 95% CI 1-10.7; p value 0.049]. Conclusion Our study confirmed that COVID-19 is generally less severe in children, although complications can develop, especially in those with comorbidities (chronic diseases or prematurity) and coinfections. Variation at the OAS1/2/3 genes cluster is the main genetic risk factor predisposing to COVID-19 pneumonia in children.